2009
DOI: 10.1177/000841740907600s09
|View full text |Cite
|
Sign up to set email alerts
|

Client-centred home modifications improve daily activity performance of older adults

Abstract: Background Remaining at home is a high priority for many older adults, but the capacity to “age in place” often is threatened by environmental barriers. Purpose To describe a client-centered occupational therapy, home modification intervention program and examine the impact of the intervention on daily activity performance over time. Methods Using a competence-environmental press framework, a client-centered home modification program for older adults was implemented. In this quasi-experimental, single grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 40 publications
4
37
0
Order By: Relevance
“…This is in line with the aims of the intervention to promote safe and independent living for people with disabilities in ordinary housing [8], and in line with previous research on how HAs are evaluated and perceived by the applicant [17,19,31,32].…”
Section: Housing Decisionssupporting
confidence: 82%
“…This is in line with the aims of the intervention to promote safe and independent living for people with disabilities in ordinary housing [8], and in line with previous research on how HAs are evaluated and perceived by the applicant [17,19,31,32].…”
Section: Housing Decisionssupporting
confidence: 82%
“…As expressed by the participants, this client-centred professional approach seemed to enhance their autonomy and control, while at the same time offering adequate, individually tailored support. Previous studies have demonstrated that a client-centred approach contributes to activity performance [7], independence [34] and autonomy [6] and increases the long-term benefits of different interventions [35]. Moreover, even when some needs had not been met, the client-centred approach used by the professionals, seemed to contribute considerably to successful intervention outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Multiple studies have also shown that HMs have a positive effect on functional outcomes. [8][9][10][11][12] Unfortunately, the delivery system for these devices has been characterized as "a patchwork of fragmented and uncoordinated services with significant gaps in types of services available and geographic coverage." 13 The burden of coordinating these services often falls to the older adults and their families.…”
mentioning
confidence: 99%